2016
DOI: 10.1016/j.ymeth.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The hematopoietic system in the context of regenerative medicine

Abstract: Hematopoietic stem cells (HSC) represent the prototype stem cell within the body. Since their discovery, HSC have been the focus of intensive research, and have proven invaluable clinically to restore hematopoiesis following inadvertent radiation exposure and following radio/chemotherapy to eliminate hematologic tumors. While they were originally discovered in the bone marrow, HSC can also be isolated from umbilical cord blood and can be “mobilized” peripheral blood, making them readily available in relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 375 publications
(221 reference statements)
2
26
0
Order By: Relevance
“…In vitro, SSCs display greater plasticity, showing higher differentiation potential than in vivo [Jiang et al, 2002;Franco Lambert et al, 2009]. Among SSCs, human mesenchymal stromal, hematopoietic and neural SCs already find an application in the clinic [Bajada et al, 2008;Thomsen et al, 2014;Porada et al, 2015].…”
mentioning
confidence: 99%
“…In vitro, SSCs display greater plasticity, showing higher differentiation potential than in vivo [Jiang et al, 2002;Franco Lambert et al, 2009]. Among SSCs, human mesenchymal stromal, hematopoietic and neural SCs already find an application in the clinic [Bajada et al, 2008;Thomsen et al, 2014;Porada et al, 2015].…”
mentioning
confidence: 99%
“…For example, pre-clinical studies suggested that HSCs from bone marrow and cord blood should have the ability to repair the infarcted heart, improving function and survival in a murine systems. Immediately, this observation triggered the launch not only of pre-clinical but, surprisingly, also of numerous clinical studies [63,64]. Based on these claims, a general debate emerged whether somatic stem cells including HSCs could have a wider, possibly even unlimited differentiation potential similar to pluripotent embryonic stem cells [65].…”
Section: Myths Facts and Future Directions Using Hematopoietic Cellmentioning
confidence: 99%
“…It is currently a matter of debate whether haematopoietic stem cells can develop into cells outside the haematopoietic lineage 32,[39][40][41][42][43][44][45] and most investigators suggest that haematopoietic stem cells cannot cross lineage boundaries. 42 In accordance with this, bulk preparations of human fat cells from BM-transplanted subjects expressed no detectable amounts of haematopoietic markers.…”
mentioning
confidence: 99%